Factors Affecting Learners With Disabilities–Instructor Interaction in Online Learning. Issue 2 (June 2017) - Alamri, Abdulrahman; Tyler-Wood, Tandra
Little research is available documenting the success of students with various types of disabilities in online classroom environments. This study investigates which factors associated with learners with disabilities impact student outcomes in an online learning environment. Forty learners with disabilities participating in online higher education coursework were asked to respond to an electronic survey of 20 questions. Results indicated that there were two factors: (1) the teaching and social presences and (2) the facilitating and supporting of individual communication related to interaction among learners with disabilities and their instructors that impacted students' perceived learning achievement and class satisfaction. Respondents also indicated that social interaction factors, such as social presence, were correlated with less perceived learning achievement and satisfaction. This study has potential value because it found factors related to learner–instructor control that may predict students with disabilities' perceived learning achievement and satisfaction.